2018
DOI: 10.1111/1468-2427.12714
|View full text |Cite
|
Sign up to set email alerts
|

The Familiar Face of the State: Affect, Emotion and Citizen Entitlements in Dehradun, India

Abstract: Municipal Councillors (MCs) are the 'familiar face of the state' in Dehradun, India: the first port of call for citizens seeking to claim entitlements from the state. The way MCs respond to the requests of their constituents is a major factor in the uneven distribution of government welfare and services. This article seeks to contribute to understandings of citizen entitlements by drawing attention to the role of affect and emotion in shaping the interactions between MCs and voters. I examine the ways citizens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…However, in the scholarship cited, affects remain undertheorized regarding the specific workings of both their emergence and impact. A recent exception, published in this journal, is Jakimow's (2020) analysis of affect in interactions between local state representatives and citizens in northern India. She points out a crucial dimension of affect that I explore in this article, concerning its co‐contingency on the distribution of power and resources.…”
Section: Affect In Urban Political Economy?mentioning
confidence: 99%
See 2 more Smart Citations
“…However, in the scholarship cited, affects remain undertheorized regarding the specific workings of both their emergence and impact. A recent exception, published in this journal, is Jakimow's (2020) analysis of affect in interactions between local state representatives and citizens in northern India. She points out a crucial dimension of affect that I explore in this article, concerning its co‐contingency on the distribution of power and resources.…”
Section: Affect In Urban Political Economy?mentioning
confidence: 99%
“…Contrary to Jakimow's (2020) detailed accounts of individual's affects, in this article I seek to understand affects as supra‐individual, relational phenomena, moods, or ‘atmospheres [that] have the potential to reinforce social inequity or build coalitions of resistance’ (Leff, 2021: 1). This supra‐individual perspective seems counterintuitive, considering the very corporal definition of affect as the ‘capacity which a body has to be affected … and to affect …’ (Anderson, 2006: 735), which, contrary to emotion, is considered non‐ or pre‐cognitive (Pile, 2010).…”
Section: Affect In Urban Political Economy?mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, studies have revealed the often ambiguous role that collective affects such as fear (Azab & Santoro, 2017), rage (Lloyd, 2019) and hope (Airas, 2019) play in the everyday of political movements. Following this affective turn in politics, urban scholars have explored the affective and emotional dimensions of urban governance systems (Jakimow, 2020;Tucker, 2017). Jakimov (2020, p.430) has argued that "affective and emotional animations" are overlooked aspects of state-society relations which "shape citizens' [differentiated] access to government services".…”
Section: The Politics Of Affective Governancementioning
confidence: 99%
“…Recently, studies have revealed the often ambiguous role that collective affects such as fear (Azab and Santoro, 2017), rage (Lloyd, 2019) and hope (Airas, 2019) play in the everyday of political movements. Following this affective turn in politics, urban scholars have explored the affective and emotional dimensions of urban governance systems (Jakimow, 2020;Tucker, 2017).…”
Section: The Politics Of Affective Governancementioning
confidence: 99%